The strengths of security personnel in tertiary institution: a case study of Kwara State Polytechnic, Nigeria / Amin Amin and Abdulkadir Kolawole Ajadi - Amin, Amin; Ajadi, Abdulkadir Kolawole (Faculty of Administrative Science and Policy Studies, 2025)
The paper examined the types of training, capacity of security, impact, and challenges confronting security at Kwara State Polytechnic. The study is a descriptive research design Both primary and secondary data were used. The questionnaire was analyzed by using Statistical Package for Social Sciences (SPSS) Version 22. Findings from the study showed that the majority of the respondents agreed that the security personnel receive orientation before engaging in any task. The respondents agreed that the school management has recruited more personnel to enhance security on the campus agreed. The majority of the respondents agreed that security personnel have been able to curb cultism operations in the campus and its environs and agreed that the security personnel can maintain a good relationship with transporters (bus and taxi drivers, keke NAPEP operators) to ensure the smooth running of academic activities The study also reveals that majority of the respondents agreed that students’ harassment is one of the challenges facing security unit and respondents agreed that lack of proper identification of staff affects security operation and also agreed that inadequate patrol vehicles hinder effective security operation in the campus The paper concludes that security personnel are working effectively to maintain peace and prevent any form of riot in the Polytechnic community. The paper recommended that much emphasis should be laid on students’ orientation rather than matriculation and the management should introduce a functioning security office to every institute on the campus